2022
DOI: 10.3389/fmed.2022.988507
|View full text |Cite
|
Sign up to set email alerts
|

Anti-colorectal cancer effects of seaweed-derived bioactive compounds

Abstract: Seaweeds are classified as Chlorophyta, Rhodophyta, and Phaeophyta. They constitute a number of the most significant repositories of new therapeutic compounds for human use. Seaweed has been proven to possess diverse bioactive properties, which include anticancer properties. The present review focuses on colorectal cancer, which is a primary cause of cancer-related mortality in humans. In addition, it discusses various compounds derived from a series of seaweeds that have been shown to eradicate or slow the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 171 publications
0
10
0
Order By: Relevance
“…Similarly, other components of the seaweed extracts, such as pigments or polyunsaturated fatty acids, have shown relevant antitumoral activity by interference with several signaling pathways related to cell proliferation and apoptosis. They can also enhance the apoptotic mechanisms induced by different chemotherapeutic drugs [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, other components of the seaweed extracts, such as pigments or polyunsaturated fatty acids, have shown relevant antitumoral activity by interference with several signaling pathways related to cell proliferation and apoptosis. They can also enhance the apoptotic mechanisms induced by different chemotherapeutic drugs [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…The space environment exposes living organisms to a very different environment from Earth for a long time, which makes a food ingredient that meets daily needs while helping astronauts reduce the risk of cancer (Mitchell et al ., 2019), cardiovascular dysfunction (Zhu et al ., 2015) and immune dysfunction (Ludtka et al ., 2021) caused by space radiation a better choice. A variety of bioactive substances in seaweeds have been proven to have anticancer effects through various mechanisms, including inhibiting the invasion and replication of cancer cells (Fu et al ., 2022). For example, a variety of seaweed polysaccharides and carotenoids have been confirmed to inhibit the proliferation of cancer cells by regulating the PI3K/AKT apoptosis pathway (Liu et al ., 2022).…”
Section: Prospects For Seaweed Applications In the Futurementioning
confidence: 99%
“…Increasing studies have proved that NPs kill tumor cells through a variety of molecular mechanisms, including cell DNA damage and apoptosis, such as matrine ( Li, Lai et al, 2016 ) and curcumin ( Zhao, Chen et al, 2015 ). In addition, Dai ( Fu, Xie et al, 2022 ) reported anti-colorectal cancer effects of seaweed-derived bioactive compounds; Kang ( Lee, Jayawardena et al, 2022 ) reported that marine algae extracts could alleviate high-fat-induced obesity. In the present study, we isolated 32.5 mg of the monomeric compound AC from the Alstonia yunnanensis Diels roots.…”
Section: Disscussionmentioning
confidence: 99%